LOCAL GOVERNMENTS WITHOUT GOVERNANCE IN SINDH - Jalil Ahmed Chandio; Siraj Ahmed Soomro; Allah Dino (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
This research paper aims to determine the weaknesses and some strengths of the Local Government Governance in Sindh. It is indicating the reasons why the local government system is failing in Sindh for example, conflicts of the political parties like PPP, MQM etc. It is defining the Local Government Act 2013 of Sindh and the major findings related to the political system, lacking the capabilities of local government and other important knowledge to show that how local governments ion Sindh has no governance. This study is, therefore, is also giving some guideline to the current government of Pakistan in order to increase the resources and funding to the local governments of Sindh for the purpose their improvements for the whole society or state.